Women's Satisfaction Regarding Care Provided by Nurse-Midwives During Labor in Bint AL-Huda Hospital in AL Al-Nasiriyah City - naeem, fatima; khairi, Suhad (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: To assess the woman satisfaction with nursing care during labor.Methodology: A descriptive analytic study about conducted for a purposive (non probability) sample of one hundred  labor women interview validity and reliability of questionnaire are determined through panel of experts and pilot study. Descriptive and inferential statistical procedures were used to analyze the data, which collected by using interview technique.Results: The study sample indicated that in general the women were satisfied in nursing care that provided during labor.Recommendations: The study recommended educational training courses for nurse-midwife to teach how deal with patient and develop skills of communication, listening and interpersonal relationship, provide support, fully understanding the expectations, privacy during delivery procedures, continuity assurance about baby, explain what happen after each examination and keep the delivery room claim and quiet light with further studies to improve nursing care.